Rural Field Experiences: Promising Practices - Janet K Stramel; Paul Adams (The Advocate, 2020)
A Rural Field Experience, in which pre-service teachers are totally immersed in the rural school setting and rural life, has been successful in attracting and retaining mathematics and science teachers in rural schools. The week-long Rural Field Experience is having a lasting effect on recruiting and retaining teachers. Responses from teacher education candidates indicate that successful strategies for building partnerships support this program and approach. Funded by an NSF Robert Noyce Scholarship grant, this program includes unique courses focused on issues related to teaching in a rural community.
Keywords: Clinical Experiences; Teacher Education; Rural